Women's land rights in the transition to individualized ownership: implications for the management of tree resources in western Ghana - Quisumbing, Agnes R.; Payongayong, Ellen; Aidoo, J. B.; Otsuka, Keijiro (International Food Policy Research Institute, 1999)
This study explores the impact of changes in land tenure institutions on women's land rights and the efficiency of tree resource management in Western Ghana. We find that customary land tenure institutions have evolved toward individualized systems to provide incentives to invest in tree planting. However, contrary to the common belief that individualization of land tenure weakens women's land rights, these have been strengthened through inter vivos gifts and the practice of the Intestate Succession Law. Investment in tree planting, in turn, is affected not simply by the level of land tenure security, but also by its expected changes, as tree planting strengthens land tenure security. Cocoa yields are lower on allocated family land and rented land under share tenancy due to distorted work incentives. While men and women are equally likely to plant trees, women obtain lower yields on their cocoa plots, suggesting the presence of gender-specific constraints.